Admissibility of computer and other electronically stored information in Nigerian courts: victory at last (2011)
There is no doubt that Nigeria is getting her own share of action of the fast-growing Information and Communication Technology. These days, financial transactions, communication system and business activities are done electronically. The growth in the amount of computer and other electronically generated evidence in the last three decades had reduced the entire universe into a global village. Contracts and other business transactions are concluded electronically, professionals such as lawyers, bankers, accountants and other allied experts receive instructions for work electronically, accept instructions electronically and send completed work to their clients via computer and other electronic devices. Courts are not left behind as they also face serious challenges foisted on them due to technological advancement and the introduction of electronically generated evidence. The issue of admissibility of evidence is crucial to judicial proceeding as it has the capacity to determine the outcome of a case one way or the other. This article therefore aims at examining the admissibility of computer and other electronically generated evidence under the newly promulgated Evidence Act of 2011. For the purpose of clarity and appreciation of the issues surrounding the amendment of Evidence Ordinance of 1943 1, the paper will go down the memory lane to chronicle agitations and criticisms that led to the amendment of the Evidence Act inherited from the colonial government in 1943 in order to bring its provision at par with advancement in Information Communication Technology worldwide.